The Dynamics of Young Generation Social Transformation in the Era of Globalization in Batik Laweyan Village Surakarta - Novita, Wida Dwi; Assalim, Nafila Saniya (HISTORIA: Jurnal Program Studi Pendidikan Sejarah, 2025)
This research aims to analyze the transformation of the younger generation's role in developing and preserving Kampung Batik Laweyan in the era of globalization. The results obtained from this research will focus on several key issues; 1) the transformation of the youth's role in the development of Kampung Batik Laweyan in the era of globalization; 2) the role of the younger generation in the development of Kampung Batik Laweyan; and 3) the youth development system in Kampung Batik Laweyan. The method used in this research is qualitative with a descriptive analysis approach. Data collection processes include observation, interviews, and literature review. After obtaining the data, the research involves data reduction, data presentation, verification, and drawing conclusions. The results of this research contribute to understanding the social transformation occurring in the younger generation in Laweyan concerning the development of Kampung Batik Laweyan.